O elo (des)construído: trajetórias de jovens trabalhadores acidentados no contexto do mundo do trabalho e da Reabilitação Profissional do INSS - Paula, Renata Soraia de (2019)
This essay presents an analysis of the professional paths of young employees, who have been involved in an accident at work and are registered in the Professional Rehabilitation Program (Programa de Reabilitação Profissional) of Brazilian Social Security Institute (Instituto Nacional de Seguro Social – INSS / Agência da Previdência Social - APS) in Guarulhos city of São Paulo. Hereby, the social security services is been contextualized in its historical-political, theoretical-methodological and practical foundations, still including some reflections about the structural weakening of the labor market while in the dynamics of capitalism and its impacts on the social policies, particularly, to the Brazilian Social Security. The study assumes that the professional rehabilitation has a direct connection to the recent phenomenon of labor market, and this has determined the understanding about the young employee‟s particularities, mainly, the work conditions, social relationships (work-health, family, community etc.), difficulties and efforts for a job replacement. For this, a bibliographic review and a documentary research in primary and secondary data sources took place, including access to updated statistical data. Alongside, to support the qualitative research, interviews were held with two young participants of the professional rehabilitation program. At last, the research showed that: a) the precarious conditions and the work setup imposed to the employees endorse the occurrence of accidents at work; b) the idea of weakening the labor relations in the modern world impacts on the (re) construction of young employees professional paths; c) due to the difficulties of professional rehabilitation inside the companies where young employees are inserted, as well as, the situation of the labor market, mainly during youth (high unemployment level, informal jobs, and poor labor relations), it is crucial that the State (Public Ministry, Ministry of Employment and related organs) including labor unions and civil society take concrete and permanent actions to widen the inspection on the companies, therefore, the quotas law can be implemented, assuring replacement for employees under rehabilitation or with disabilities; d) discussions about the professional rehabilitation service, based on social policies to youth segment, foresee possibilities of multisector and educative actions for the effective protection of employees under rehabilitation and with disabilities